Follow the Mass—A Concordance Picture of Tidal Disruption Events - Julian Krolik; Tsvi Piran; Taeho Ryu (The Astrophysical Journal, 2025)
Three recent global simulations of tidal disruption events (TDEs) have produced, using different numerical techniques and parameters, very similar pictures of their dynamics. In typical TDEs, after the star is disrupted by a supermassive black hole, the bound portion of the stellar debris follows highly eccentric trajectories, reaching apocenters of several thousand gravitational radii. Only a very small fraction is captured upon returning to the vicinity of the supermassive black hole. Nearly all of the debris returns to the apocenter, where shocks produce a thick irregular cloud on this radial scale and power the optical/UV flare. These simulation results imply that over a few years, the thick cloud settles into an accretion flow responsible for the long-term emission. Despite not being designed to match observations, and without any free parameters, the dynamical picture given by the three simulations aligns well with observations of typical events, correctly predicting the flares’ typical total radiated energy, luminosity, temperature, and emission-line width. On the basis of these predictions, we provide an updated method ( TDEmass ) to infer the stellar and black hole masses from a flare’s peak luminosity and temperature. This picture also correctly predicts that the luminosity observed years after the flare should be nearly constant. In addition, we show that in a magnitude-limited survey, if the intrinsic rate of TDEs is independent of black hole mass, the detected events will preferentially have black hole masses ∼10 ^6.3±0.3 M _⊙ and stellar masses ∼1 M _⊙ .